Pengaruh Kepemilikan Manajerial terhadap Nilai Perusahaan di Mediasi oleh Kebijakan Dividen - Ramadhani, Fitri Kurnia; Mismiwati, Mismiwati (Universitas muhammadiyah palembang, 2019)
The aim of this research to determine the effect of Managerial Ownership (MOWN) on Company value (Tobins) mediated by devidend Policy (DPR) in companies listed in the Jakarta Islamic Index (JII) for perid of 2013-2017. The population on this study were 14 companies with 7 companies that became the study sample. Samples were taken by purposive sampling. The method used is quantitative by emphasizing numeral data. The data used in this study are secondary data taken from the official website of the Indonesia Stock Exchange. The data analysis technique using the path analysis test. The results showed that managerial ownership had a significant positive effect on firm value; Managerial ownership has a significant positive effect on Devidend Policy; Devidend policy has a positive effect on company value; and Devidend policy mediates between managerial ownership of company value.